Under the Semantics of Ethnic Architecture of Pribaikalie - Kulesh, Darya (project baikal, 2015)
The article studies traditional ethnic architecture of Pribaikalie, which recreates age-old world views and acts as a primary element of archaic culture.
Keywords: archaic model of the universe; mythopoetic epic; poetics of the space; architectural semantics; ethnic architecture; traditional dwelling